UPAYA MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS, KOMUNIKASI DAN KARAKTER CITIZENSHIP SISWA SEKOLAH DASAR MELALUI IMPLEMENTASI MODEL PEMBELAJARAN BATIK - Muhammad Fauzan Lavionda Arsyad; Akhmad Riandy Agusta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve student activity, critical thinking skills, citizenship, communication, and learning outcomes in Pancasila Education at SDN Murung Sari 4. The identified problems included low student engagement and unsatisfactory learning outcomes due to monotonous teaching methods, limited interaction, and classroom conditions that did not support active student participation. To address these issues, the BATIK learning model was implemented, which combines Problem-Based Learning (PBL), Two Stay Two Stray (TSTS), and the Talking Stick method. This research employed a Classroom Action Research (CAR) design conducted over three meetings involving seven fifth-grade students in the even semester of the 2024/2025 academic year. Data collection techniques included observations of teacher and student activities, tests of critical thinking skills, citizenship, communication, and learning outcomes. Data were analyzed using qualitative descriptive and quantitative percentage techniques. The results showed that the implementation of the BATIK model successfully increased student activity from “less active” to “very active.” In addition, students' critical thinking, citizenship, and communication skills improved to the “good” and “very good” categories. Student learning outcomes also experienced continuous improvement in each meeting. Based on these results, the BATIK model is considered effective for enhancing student activity, skills, and learning outcomes, and is recommended as an innovative teaching strategy to support the implementation of the Merdeka Curriculum.